Trans-Spinal Direct Current Stimulation For Enhancing Motor Function After Anterior Cervical Discectomy And Fusion: A Narrative Review (International Journal of Environmental Sciences, 2025)
Purpose of review: Trans-spinal direct current stimulation (tsDCS) has attracted growing interest as a potential neuromodulatory intervention for spinal cord injuries, especially in postoperative rehabilitation. Recently, its role in enhancing motor recovery following spinal surgeries—particularly anterior cervical discectomy and fusion (ACDF)—has gained significant attentionMethods: comprehensive search of Science Direct, PubMed, and Google Scholar was conducted using keywords such as neuromodulation, trans spinal direct current stimulation, anterior cervical discectomy and fusion, motor improvement. Articles published from February 2011to, December 2024 were included, and only English-language studies were reviewed. Unpublished manuscripts, conference abstracts, and studies not involving larger scientific investigations were excluded.Results: The evidence suggests that trans-spinal direct current stimulation (tsDCS), when integrated with conventional rehabilitation approaches, may enhance motor function in patients following anterior cervical discectomy and fusion (ACDF). Nonetheless, current findings are preliminary, and further large-scale, methodologically robust studies are required to validate these outcomes and develop standardized clinical protocols.Conclusion: Current evidence supports the use of trans-spinal direct current stimulation (tsDCS) as a promising neuromodulatory approach that may serve as an adjunct to enhance motor recovery following spinal surgeries, particularly anterior cervical discectomy and fusion (ACDF). However, further high-quality clinical trials are necessary to confirm its therapeutic efficacy and elucidate the underlying neurophysiological mechanisms.